Analisis Hubungan Antara Pendidikan Vokasional Agribisnis Dan Peningkatan Pendapatan Petani - Tika Leoni Putri; Eni Puji Rahayu; Dinda Rida Safira; Aan Budianto (CV. Creative Tugu Pena, 2022)
This This study aims to analyze the relationship between vocational agribusiness education and the improvement of farmers’ income in 2022. Using a descriptive qualitative approach, data were collected through in-depth interviews, field observations, and documentation involving 15 farmers who participated in vocational training programs. The findings indicate that most farmers experienced an increase in technical and managerial skills after attending the training, including improved cultivation practices, cost efficiency, basic financial management, and product marketing strategies. As a result, the majority of farmers reported a 10% to 30% increase in their income. However, the success of vocational training was also influenced by external factors such as infrastructure, market access, and institutional support. The study concludes that vocational agribusiness education plays a significant role in empowering farmers and enhancing their economic capacity, especially when integrated with a supportive agribusiness ecosystem. Therefore, it is recommended that vocational training be developed contextually, tailored to local needs, and supported by inclusive rural development policies